2005
DOI: 10.1016/j.cub.2005.02.018
|View full text |Cite|
|
Sign up to set email alerts
|

The Zebrafish-Secreted Matrix Protein You/Scube2 Is Implicated in Long-Range Regulation of Hedgehog Signaling

Abstract: The Hedgehog (Hh) signal plays a pivotal role in induction of ventral neuronal and muscle cell types around the midline during vertebrate development [1]. We report that the gene disrupted in zebrafish you mutants, in which Hh signaling is impaired, encodes the secreted matrix protein Scube2. Consistently, epistasis analyses suggested that Scube2 functions upstream of Hh ligands or through a parallel pathway. In addition, overexpression analyses suggested that Scube2 is an essential, but a permissive, mediator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
76
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 35 publications
11
76
0
Order By: Relevance
“…It is of interest to further examine whether the CUB-mediated BMP binding/antagonism could be extended to other members of the TGF-␤ superfamily. Our deletion analysis and biochemical/molecular data are broadly in line with genetic evidence (14), thus confirming that the 6-cysteine repeat motifs and CUB domain are essential for the SCUBE function in attenuating BMP activity when co-expressed in the same cells (Fig. 7).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…It is of interest to further examine whether the CUB-mediated BMP binding/antagonism could be extended to other members of the TGF-␤ superfamily. Our deletion analysis and biochemical/molecular data are broadly in line with genetic evidence (14), thus confirming that the 6-cysteine repeat motifs and CUB domain are essential for the SCUBE function in attenuating BMP activity when co-expressed in the same cells (Fig. 7).…”
Section: Discussionsupporting
confidence: 68%
“…Molecular Analysis of the C-terminal Six-cysteine Repeat Motif and CUB Domain-Recent genetic analysis identified that the zebrafish orthologue of the mammalian SCUBE2 gene acts upstream of hedgehog ligands or through a parallel pathway (13)(14)(15). In addition, a nonsense mutation in the ty97 allele encodes a truncated null protein lacking the cysteine-rich repeat motif and the CUB domain, implying that this C-terminal region is essential for SCUBE2 function (13)(14)(15).…”
Section: Establishment Of Cell Lines Expressing a Series Of Scube1 Egmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual Scube members have distinctive expression profiles, with transcripts identified in mouse, rat and zebrafish embryos within a diverse array of tissues and suggesting that this family may encode proteins with important roles during embryonic development (Xavier et al 2010(Xavier et al , 2009Haworth et al 2007;Hollway et al 2006;Woods and Talbot 2005;Kawakami et al 2005;Wu et al 2004;Grimmond et al 2001). Scube2 transcripts have been identified primarily in forebrain and trunk neuroepithelium and the anterior hindbrain of the mouse embryo, becoming progressively localized to the dorsal forebrain, hindbrain caudal to rhombomere 1 and neural tube (Grimmond et al 2001).…”
Section: Introductionmentioning
confidence: 98%
“…The Scube (Signal peptide CUB EGF-like domain-containing protein) family consists of three independent members evolutionarily conserved from zebrafish to humans (Xavier et al 2010(Xavier et al , 2009Haworth et al 2007;Woods and Talbot 2005;Kawakami et al 2005;Wu et al 2004;Grimmond et al 2001Grimmond et al , 2000. Within this family, Scube2 was originally identified following an electronic database search using the Scube1 nucleotide and predicted amino acid sequence.…”
Section: Introductionmentioning
confidence: 99%